Transapical transcatheter aortic valve implantation using the J-Valve system: A 1-year follow-up study - Luo, Xiang; Wang, Xu; Li, Xuan; Wang, Xin; Xu, Fei; Liu, Mingzheng; Yu, Bing; Li, Fei; Tong, Minghui; Wang, Wei (The Journal of thoracic and cardiovascular surgery, 2017)
Transcatheter aortic valve implantation has become a routine procedure to treat screened inoperable or high-risk patients. In this study, we present the first outcome of echocardiographic midterm using a new second-generation transcatheter aortic valve implantation system, the J-Valve system (Jie Cheng Medical Technologies, Suzhou, China), in patients with aortic stenosis or aortic regurgitation. From July 2014 to June 2015, 21 patients with isolated aortic valve disease at high risk for open surgery received transapical transcatheter aortic valve implantation using the J-Valve system. The primary end point was a combined efficacy end point after 1 year, which included all-cause mortality after more than 30 days and failure of current therapy for aortic stenosis or aortic regurgitation requiring hospitalization for symptoms of valve-related cardiac decompensation or prosthetic heart valve dysfunction. Secondary end points were cardiovascular mortality, major stroke, and life-threatening, disabling, or major bleeding after 6 and 12 months. The mean age of the study cohort was 75.52 ± 5.22 years, the European System for Cardiac Operative Risk Evaluation II score was 11.33% ± 1.28%, and the mean logistic European System for Cardiac Operative Risk Evaluation I score was 31.13% ± 9.68%. Transcatheter aortic valve implantation with the J-Valve system was successfully performed in 19 of the 21 patients (90.5%). For patients with aortic stenosis, 12-month follow-up echocardiography demonstrated an increase in mean effective valve area from 0.62 ± 0.17 cm2 to 1.52 ± 0.35 cm2 and a decrease in transvalvular mean gradient from 61 ± 15 mm Hg to 18 ± 9 mm Hg. All surviving patients (n = 18) reported improvements in at least 1 of the New York Heart Association classes. The combined ratio of successful implantation and absence of adverse events in our cohort (n = 21) was 76.19%. The J-Valve system exhibits a convincing midterm performance and is a safe and feasible procedure with low perioperative and postoperative complications.